Spinal Anaesthesia for Emergency Caesarean Section in a Morbid Obese Woman with Severe Preeclampsia - Ebirim N. Longinus; Lagiri Benjamin; Buowari Yvonne Omiepirisa (Case Reports in Anesthesiology)
Background. Morbid obesity in a pregnancy is a great challenge to medical practice especially when the patient requires caesarean section. Case Summary. A 38-year-old unbooked gravida 3 Para 2+0 weight 195 kg, height 1.7 m with a blood pressure of 210/160 mmhg had spinal anaesthesia for emergency caesarean section which was technically difficult for severe preeclampsia at 32-week gestation. She had poor wound healing and spent 18 days postoperatively on hospital admission. Conclusion. Morbid obesity is a challenge to both obstetric and anaesthetic practice. Antenatal care is necessary in reducing both maternal morbidity and mortality.